EFL University Learners As Researchers: Teaching Process Advantages - Ruzhekova–Rogozherova, Boryana (Research Papers, 2023)
The paper focuses on presuming teaching process advantages of university learners’ research in the context of English as a Foreign Language (EFL) training, comprising, in the author’s situation, English for General Purposes (EGP) and English for Specific Purposes (ESP), based on existing data. Research concept is defined and its characteristics are outlined in terms of student research relevance. Examples of EFL university student research tasks are provided. Students’ research benefits are considered mainly with respect to language awareness (LA) and learner autonomy (LrA) enhancement. Conclusion treats the expected connectedness between EFL learner research and learners’ communicative competence improvement.
Keywords: Learner research; EFL learner research; Language awareness; Learner autonomy; Teaching process effectiveness